Voice-Over Text in Documentary Film Discourse - M. G. Urtmintseva; V. N. Skachkova (Научный диалог, 2022)
The article is devoted to the characteristics of the voice-over text functions as a way to embody the film discourse of a documentary film that recreates the image of M. Gorky during the last ten years of his life. The material of the study was the correspondence of M. Gorky in 1924–1927 with writers, where his attitude to the transformations in the Soviet Union and work on the story “The Life of Klim Samgin” were discussed. In order to restore the amount of material underlying the script, work was carried out to decipher the sounding voice-over text, the addressees of the letters, the dating of the correspondence were established, and the fragments included in the voice-over text were compared with the full text of the letters. As a result of the study, it was proved that the voice-over text, considered in the history of documentary cinema as an auxiliary element of the video sequence, in the film by S. Aranovich and B. Dobrodeev acts as the main semantic element of the narrative, built on the principle of editing fragments of the epistolary, arranging them according to the problem-thematic principle with a violation of the chronology of correspondence. The most important feature of the documentary discourse of the film is the combination within one episode of fragments of quotations from M. Gorky’s letters to different addressees, which is dictated by the author’s concept of the image of the writer as a tragic personality who turned out to be a hostage of the myth created about him as a proletarian writer, a defender of the Bolshevik ideology.